THE EFFECT OF HUMANISTIC APPROACH ON STUDENTS’ LEARNING MOTIVATION OF CLASS XI OF SMA NEGERI 3 TARUTUNG DURING COVID-19 PANDEMIC - Aritonang, Oktober Tua (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: The purpose of study is to determine whether there is a positive and significant effect of humanistic approach on learning motivation of class XI students of SMA Negeri 3 Tarutung during Covid-19 pandemic. This research is quantitative descriptive by using descriptive statistic method. The population is 143 students of class XI and the sample of 25%, namely 36 students were taken randomly. A closed questionnaire was used as the instrument for the data collection. The data processing and analysis techniques used simple linear regression method with t-test. The regression equation was Y = 2.5 + 0.21 X + e. The value of X was positive value, it indicated that the better humanistic approach is applied, the more student motivation will be. Based on the data analysis, it was known that the significance value of the humanistic approach variable was 0.047. The results show that the significance value (0.047) is smaller than the value of 0.050 (α). Therefore, it is concluded that H0 is rejected and Ha is accepted. It means that the humanistic approach has a positive and significant effect on students’ learning motivation. Abstrak: Tujuan penelitian ini untuk mengetahui ada tidaknya pengaruh yang positif dan signifikan pendekatan humanistik oleh guru terhadap motivasi belajar siswa kelas XI SMA Negeri 3 Tarutung pada masa pandemi Covid-19. Penelitianini deskriptif kuantitatif dengan menggunakan metode statistik deskriptif. Populasi 143 siswa kelas XI dan sampel 25 % yaitu 36 orang diambil secara random.Teknik pengumpulan data dengan angket tertutup. Teknik pengolahan dan analisis data menggunakan metode regresi linier sederhana dengan uji-t. Persamaan regresi yaitu Y = 2,5 + 0,21 X + e. Nilai X adalah nilai positif, ini menunjukkan bahwa semakin baik pendekatan humanistik dilakukanguru akan mengakibatkan motivasi belajar siswa semakin meningkat.Dari hasil analisis diketahui bahwa nilai signifikansi variabel pendekatan humanistik oleh guru adalah sebesar 0,047. Karena nilai signifikansi 0,047 lebih kecil daripada nilai 0,050 (α) maka disimpulkan bahwa H0 ditolak dan Ha diterima. Ini berarti bahwa pendekatan humanistik oleh guru mempunyai pengaruh yang positif dan signifikan terhadap motivasi belajar siswa.